The rise and fall of Falmouth, Jamaica : urban life in 19th century Jamaica - Robinson, Carey (Kingston, Jamaica : LMH Pub., 2007)
The Rise and Fall of Falmouth, Jamaica is an attempt by writer and historian Carey Robinson to document the evolution of Falmouth from its 'hey days' - the year of the English Invasion in 1655 - to the start of the twentieth century when Falmouth Court House was destroyed by fire ...
Includes bibliographical references (pages 148-149) and index.
NLJCols20082021
Keywords: Falmouth (Jamaica) -- History; Jamaica -- Falmouth; Jamaica (Falmouth) -- History; History